PENGARUH TERPAAN BERITA KEBOCORAN DATA PENDUDUK DAN TERPAAN NEGATIVE E-WORD OF MOUTH DI MEDIA SOSIAL TERHADAP TINGKAT KEPERCAYAAN MASYARAKAT PADA PEMERINTAH PUSAT DALAM MENANGANI KASUS KEBOCORAN DATA - Vidiana Girinda Wardani; Hedi Pudjo Santosa; Djoko Setyabudi (Interaksi Online, 2023)
The Ministry of Communication and Informatics is in the spotlight amid the many cases of data leakage involving various parties. According to data, there were 1.04 million accounts that experienced data leaks in Indonesia during the second quarter of 2022. Various media reports on data leak cases highlighted how, responses, and steps were taken to handle the case. The news caused unrest among the people. Coupled with the existence of communication by word of mouth (e-word of mouth) electronically as a more efficient media channel for voicing opinions because the scope is wider and easier to reach. The purpose of this study was to determine the effect of exposure to population data leaks and exposure to negative e-word of mouth on social media on the level of public trust in the central government in dealing with data leaks. Using the theoretical approach of the Social Mediated Crisis Communication Model (SMCC), this study examines the effect of variable X1 and variable X2 on variable Y. The population of this study were social media users aged 18 to 35 years, with a non-probability sampling technique on 100 people, both men and women who had been exposed to news of data leaks. The results showed that exposure to data leakage news and exposure to negative e-word of mouth had an effect on the level of trust. Furthermore, it is known that the coefficient X1 is -0.527 and the X2 variable is -0.719, which means that exposure to data leak news (X1) and exposure to negative e-word of mouth (X2) have a negative effect on the level of public trust. With these findings, it can be concluded that the higher the exposure to data leak news received by the public and the higher the exposure to negative w-word of mouth, the lower the level of trust.